CANCER OF ESOPHAGUS: TEN YEARS EXPERIENCE AT CENAR, QUETTA - ullah, Roh; Khursheed, AK; Burdey, GM; Hamdani, SRH; Javaid, Javaid; Kamran, S; Nusrat, J (Journal of Ayub Medical College Abbottabad, 2001)
Background: A retrospective study of 659 patients of Ca Esophagus was conducted from 1 January 1990 to 31s' December 1999 (10 years) at CENAR Quetta. The aim of this study was to highlight the incidence, early detection, management, and various other parameters of Ca Esophagus. Results: During this period, 5819 new eases of cancer were registered. Cases of Ca Esophagus constituted 659 (11.32 %) in number. It was studied that this cancer was the 3th most common cancer registered in both sexes at our centre. 65 new cases of Ca Esophagus were registered at CENAR Quetta per annum on an average. Males slightly dominated the females. Maximum number of cases 470 (71.31 %). were reported between ages 4 1 - 6 0 years with a median age of 55 years. Maximum number of cases 399 (60.57 %), involved lower 3' of Esophagus. Squamous cell carcinoma was the most common histopathology seen in 574 cases (87.10 %). These patients were mainly treated with radiation therapy, palliative, because by the time they reported, they were found in stage 111 and beyond. Some patients were also treated with chemotherapy along with radiation, but the overall prognosis was poor. A few patients have also undergone palliative surgery; such as pull through or push through tubes prior to radiotherapy. Conclusions: Since the patients presented with late & advanced disease, it is, therefore, recommended that all cases of dysphagia particularly from this region of the country should be thoroughly investigated with the suspicion of Ca Esophagus. It is further suggested that general population be educated about the potential risk factors like smoking, use of naswar, beetle nut chewing, and intake of very hot food & beverages